Penilaian Maturasi Tulang Vertebra Servikalis dan Maturasi Gigi pada Pasien Ortodonti Usia 9-11 tahun di RSGM-P FKG USAKTI - Annisa Nabilah Fattah; Olivia Piona Sahelangi (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: The period of growth spurt is an important factor in helping to optimize the outcome of orthodontic treatment and can be determined through indicators of cervical vertebral maturation stage and dental maturation. According to Bacetti, Cervical Vertebral Maturation Stage (CVMS) is a method to determine cervical vertebral maturation which is categorized in cervical stages (CS) one to six using lateral cephalograms. According to Demirjian, canine maturation assessment is used to see the development of tooth mineralization which is categorized in stages A-H using panoramic radiography. Purpose: To describe the cervical vertebral maturation stage and dental maturation in orthodontic patients aged 9-11 years at RSGM-P FKG Trisakti University. Method: A descriptive observational study with a cross-sectional design and assessing the maturation of the cervical vertebrae according to Bacetti and the maturation of the canines according to Demirjian using 96 lateral cephalograms and panoramic radiographs in orthodontic patients aged 9-11 years at RSGM-P FKG Trisakti University. Result: The majority of cervical vertebral maturation stage in patients aged 9-11 years are at cervical stage two 41.7% with the majority of girls patient 37.5% being at cervical stage two and boys patient 53.1% are at cervical stage one. For canine maturation the majority are in stage F of 45.8% with the majority of girls patient 47.9% are in stage F and boys patient 47.9% are in stage E. Conclusion: Cervical vertebral maturation stage in patients aged 9-11 years the majority in girls occurs at the pre-pubertal cervical stage two and boys occur at the pre-pubertal cervical stage one. For canine maturation, it is at the pre-pubertal stage F for girls and the pre-pubertal stage E for boys.